The Attainment of Soft Skills Among Students: Impact of Abroad Study Visit Program - Abd Hadi Bunyamin, Muhammad; Rustam Mohd Rameli, Mohd; Hassan, Zainudin; Hazirah Noh@Seth, Nur; Talib, Rohaya; Mohd Yusof, Sanitah; Abu Naim, Hamimah; Md Salleh, Shaharuddin; Ali Ibrahim, Mohd; Mohd Zulkifli, Rafeizah (International Journal of Engineering and Technology, 2018)
This study aims to determine the impact of an abroad study visit program on the attainment of soft skills among the students. A questionnaire was used to collect the data using a five-scale range of answers. Thirty-five students were selected among the participants of the program. The data is analysed using descriptive and inferential statistics, namely mean, standard deviation, and correlation. The primary finding obtained is that the program has provided a huge opportunity for the students to develop their professional ethics and moral indicated through the highest mean obtained by the items related to the construct. In terms of correlations, the positive and the strongest correlation is between the construct of Critical Thinking and Problem Solving Skills and the construct of Lifelong Learning and Information Management. The implications of the findings are also discussed.Â